Genetic parameter estimates for feet and leg traits in Red Angus cattle - Jensen, Brady Robert (Kansas State University, 2017)
The objective of this study was to investigate the parameter estimates for feet and leg traits, relationships within feet and leg traits, and between feet and leg traits and production traits in Red Angus cattle. Subjective scores for 14 traits including: Body Condition Score (BCS), Front Hoof Angle (FHA), Front Heel Depth (FHD), Front Claw Shape (FCS), Rear Hoof Angle (RHA), Rear Heel Depth (RHD), Rear Claw Shape (RCS), Size of Hoof (Size), Front Side View (FSV), Knee Orientation (KNEE), Front Hoof Orientation (FHO), Rear Side View (RSV), Rear View (RV), and a Composite Score (COMP) were collected by trained evaluators on 1885 Red Angus cattle at different ranches across the United States. A three-generation pedigree file was obtained from the Red Angus Association of America (RAAA) that contained 13,306 animals, and EPDs on all animals with feet and leg scores were obtained. All traits except COMP were scored as intermediate optimum traits. Data were modeled using a linear bivariate animal model with random additive genetic and residual effects, and fixed effects of age and contemporary group (herd-year). Variances were estimated with ASREML 3.0 and 4.0. Heritability estimates of BCS, FHA, FHD, FCS, RHA, RHD, RCS, Size, FSV, Knee, FHO, RSV, RV, and COMP were 0.11, 0.20, 0.17, 0.09, 0.19, 0.25, 0.17, 0.36, 0.16, 0.17, 0.17, 0.30, 0.14, and 0.12, respectively. These results showed feet and leg traits were lowly to moderately heritable. Strong, positive genetic correlations were found between FHA and FHD (0.89), FHA and RHA (0.88), FHD and RHA (0.85), FHA and RHD (0.85), FHD and RHD (0.94), and FHO and Knee (0.95), indicating these traits may be highly related to one another. Strong negative correlations were found between Knee and FSV (-0.59) and FHO and FSV (-0.75). The strongest correlation was between front limb traits (FHA, FHD, FSV, FHO, Knee, and Comp) and the Stayability EPD (STAY) was FSV (r =0.16; r_s =0.20) and for rear limb traits (RHA, RHD, RCS, RSV, RV, and Comp) and STAY was RCS (r = -0.12; r_s=-0.14). This indicates that cattle with more slope to the angle of the shoulder stay in the herd longer and cattle with less curl to the inside of the claw tend to stay in the herd longer. Further studies with more data could help validate the relationship between feet and leg traits and production traits.
Keywords: Feet and leg structure; Beef cattle